2003
DOI: 10.1126/science.1086016
|View full text |Cite
|
Sign up to set email alerts
|

Demography of Dietary Restriction and Death in Drosophila

Abstract: Dietary restriction (DR) increases life-span in organisms from yeast to mammals, presumably by slowing the accumulation of aging-related damage. Here we show that in Drosophila, DR extends life-span entirely by reducing the short-term risk of death. Two days after the application of DR at any age for the first time, previously fully fed flies are no more likely to die than flies of the same age that have been subjected to long-term DR. DR of mammals may also reduce short-term risk of death, and hence DR instig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
458
10
11

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 511 publications
(520 citation statements)
references
References 18 publications
41
458
10
11
Order By: Relevance
“…Demographic modeling has suggested that dietary restriction in Drosophila acts by lowering age independent mortality rather than by slowing the accumulation of senescent damage (Mair et al 2003;Magwere et al 2004;Partridge et al 2005). In the present study, we did not observe such an effect.…”
Section: Discussioncontrasting
confidence: 89%
“…Demographic modeling has suggested that dietary restriction in Drosophila acts by lowering age independent mortality rather than by slowing the accumulation of senescent damage (Mair et al 2003;Magwere et al 2004;Partridge et al 2005). In the present study, we did not observe such an effect.…”
Section: Discussioncontrasting
confidence: 89%
“…This hypothesis leads to the prediction that these paradigms will cause similar changes in the mortality rate doubling time (MRDT) for a given model. When age-related changes continue at the normal rate in an experimental group but fatality due to those changes is decreased relative to controls, as was recently reported to occur in response to dietary restriction in Drosophila (Mair et al 2003), then the MRDT does not change. In contrast, when the rate of aging itself is slowed, MRDT increases.…”
Section: Discussionmentioning
confidence: 76%
“…These include screening genetic mutants for longevity phenotypes (Lin et al 1998), overexpression of genes known to enhance antioxidant defense mechanisms (Parkes et al 1998), generational selection studies (Rose et al 1992), and environmental strategies such as drug consumption (e.g., 4-phenylbutyrate; PBA; Kang et al 2002) or caloric restriction (Clancy et al 2002;Mair et al 2003). It is becoming increasingly clear that different genetic and environmental strategies for life extension lead to different patterns of gerontological decline in functional abilities of Drosophila (e.g., flight, locomotion, visuo-motor coordination, memory, and learning).…”
Section: Discussionmentioning
confidence: 99%